Unfinished business : the negotiation of the CTBT and the end of nuclear testing - Johnson, Rebecca (United Nations, 2009)
The Comprehensive Nuclear-Test-Ban Treaty (CTBT) remains a key piece of unfinished business of the nuclear age. As a growing number of governments and decision makers put forward ideas to move the world toward abolishing nuclear weapons, much can be learnt from how the CTBT was fought for, opposed and finally negotiated between 1994 and 1996. The treaty's necessity was underlined when the Democratic People's Republic of Korea conducted a nuclear test explosion in 2006, but more than a decade of political and institutional obstacles have prevented the CTBT from entering into full legal effect. New opportunities exist today for CTBT entry into force. Understanding the story of the treaty will enable civil society, governments and diplomats to assist in this process and to develop more effective strategies and tools to bring about future disarmament agreements. --